Boys Don't Cry: Examining Sex Disparities in Behavioral Oncology Referral Rates for AYA Cancer Patients - Kivlighan, Martin; Bricker, Joel; Aburizik, Arwa (Frontiers in Psychology, 2022)
Psychosocial distress is highly prevalent in cancer patients, approaching rates around 40% across various cancer sites according to multicenter studies. As such, distress screening procedures have been developed and implemented to identify and respond to cancer patients’ psychosocial distress and concerns. However, many cancer patients continue to report unmet psychosocial needs suggesting gaps in connecting patients with psychosocial services. Presently, there is a paucity of research examining sex-based disparities in referral rates to behavioral oncology services, particularly for adolescent and young adult (AYA) cancer patients. Informed by gender role conflict and empirical literature documenting disparities in cancer care and treatment based on a variety of sociocultural variables, this study aimed to examine the presence of sex disparities in referral rates to behavioral oncology services for AYA cancer patients. Data for this study consisted of 1700 AYA cancer patients (age 18-39) who completed a distress screening at a large cancer center of a teaching hospital in the Midwestern United. Results indicated that patient sex significantly predicted the odds of behavioral oncology referral (γ50 = -0.95, Odds Ratio = 2.60, p <.001). This finding indicates that female AYA cancer patients are 2.5 times more likely to be referred to behavioral oncology services compared to male AYA cancer patients after controlling for psychosocial distress and emotional, family, and practical problems. Additionally, we found that emotional problems significantly moderated the odds of referral for males and females (γ60 = 0.37, Odds ratio = 1.44, p <.001), however the odds of referral for males who endorsed emotional problems were lower than males who did not endorse emotional problems. This contrasted with female AYA cancer patients where the endorsement of emotional problems increased the odds of referral to behavioral oncology services. Findings are discussed with particular focus on how to enhance equitable care and reduce sex and other sociocultural-based disparities in AYA psychosocial oncology.